Lower limb neuromuscular control during landing movements: Do males and females respond differently to landing training programs? - Munro, B.; Stelle, J. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
Female athletes sustain injury to their anterior cruciate ligament (ACL) more frequently than their male counterparts, possibly due to hormonal influences, between-gender differences in musculoskeletal structure and/or lower limb neuromuscular patterns. It has also been speculated that differences in training regimes for males and females may also influence predisposition to ACL rupture. Therefore, this study aimed to determine whether lower limb neuromuscular patterns displayed during abrupt landing movements were affected by gender and/or participation in a landing training program. Ten male (mean 24.3 years, range 20-29) and ten female (mean 22.4 years, range 19-32) athletes with no history of knee joint disease were randomly assigned to a landing trained or control group. The landing trained group participated in a 6-week landing training program, completing three 30 minute training sessions per week. All subjects underwent laboratory-based assessment of their landing technique pre- and post-intervention, including lower limb neuromuscular patterns (1000 Hz) using the Noraxon Telemyo system. Following zero offset removal, the raw muscle burst signals were processed to obtain linear envelopes and a threshold detector determined the temporal aspects of each muscle burst with respect to initial foot-ground contact (IC) and peak resultant ground reaction force (FR; Kistler Multichannel force platform). Two-way repeated measures ANOVAs will determine if there are any significant differences (p 0.05) in the neuromuscular control patterns used by both males and females in the present study, as well as whether these are affected by participation in a landing training program.